Methotrexate and azathioprine for severe atopic dermatitis: a 5‐year follow‐up study of a randomized controlled trial. (1st June 2018) - Gerbens, L.A.A.; Hamann, S.A.S; Brouwer, M.W.D.; Roekevisch, E.; Leeflang, M.M.G.; Spuls, P.I.
Summary: Background: Systemic treatment is indicated for moderate‐to‐severe atopic dermatitis (AD) refractory to topical treatment. Long‐term evidence, up to 5 years, of off‐label prescribed methotrexate (MTX) and azathioprine (AZA) is lacking. Objectives: To investigate long‐term effectiveness, safety and drug survival of MTX and AZA. Methods: In an open‐label follow‐up phase of a clinical trial, patients were seen every 3 months for 5 years. MTX and AZA doses could be increased or decreased concurrent with daily clinical practice. Primary effectiveness outcomes were mean absolute and relative reduction in SCORing Atopic Dermatitis (SCORAD) index and Investigator's Global Assessment (IGA) after 5 years compared with baseline. To assess safety, the type, frequency, severity and relatedness to treatment of adverse events were investigated. Drug survival was analysed by Kaplan–Meier curves. Results: Thirty‐five of 43 originally included patients participated, of whom 27 completed the follow‐up. At year 5, the mean relative reduction in SCORAD index was similar in the MTX and AZA groups: 53% and 54% using descriptive analysis. Twelve serious adverse events occurred in 5 years; for three there was a possible causal relationship. Drug survival demonstrated a longer survival for MTX, but survival in both groups was low after 5 years (MTX n = 5, AZA n = 1). Conclusions: Based on this relatively small pragmatic study, MTX and AZA seem to be effective and safe as maintenance treatments in moderate‐to‐severe AD up to 5 years. Few patients in both groups survive on their originally allocated drug although some discontinued because of controlled AD.